If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 4) = (b + 4) * 2 Reorder the terms: 3(4 + b) = (b + 4) * 2 (4 * 3 + b * 3) = (b + 4) * 2 (12 + 3b) = (b + 4) * 2 Reorder the terms: 12 + 3b = (4 + b) * 2 Reorder the terms for easier multiplication: 12 + 3b = 2(4 + b) 12 + 3b = (4 * 2 + b * 2) 12 + 3b = (8 + 2b) Solving 12 + 3b = 8 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 12 + 3b + -2b = 8 + 2b + -2b Combine like terms: 3b + -2b = 1b 12 + 1b = 8 + 2b + -2b Combine like terms: 2b + -2b = 0 12 + 1b = 8 + 0 12 + 1b = 8 Add '-12' to each side of the equation. 12 + -12 + 1b = 8 + -12 Combine like terms: 12 + -12 = 0 0 + 1b = 8 + -12 1b = 8 + -12 Combine like terms: 8 + -12 = -4 1b = -4 Divide each side by '1'. b = -4 Simplifying b = -4
| -4x-7=12 | | =2x-8xy | | 4/21-h/24 | | 2x+2-2(-5x-5)=2(x-3) | | 6a-4b+a-5b= | | 6t+16=9 | | 1/5/1 | | (3/4)t+(1/8)=(3/4)(t+8) | | m/4=9/5 | | -1/5/-1 | | 6+16=9 | | 20=-2v | | -2x=-2+5 | | 0=-6n-2n | | 2x+9-2=31 | | 4.4x+64=19.36+8x | | x+(3x^1/2)-10 | | 2+6d-4= | | 9/11*14.4=-12 | | 4(x+2)-6=2x | | -4=6b-4+2b | | 9/2d=27 | | m/4=h/24 | | s+2/1/2s+10=31 | | 9(2/3) | | -x-24=-8 | | 20+5n=6n-3(n-4) | | (x^7z^5)/(x^6z) | | a-4/5=14 | | 7/15x/-1/5=4 | | 6/7(84+35y) | | 6r+-1s+9r+-3s= |